Balinese local wisdom and their implications in science education at school - Suastra, I Wayan (International research journal of management, IT and social sciences, 2017)
This study was aimed to dig Balinese local wisdom, to reconstruct, and develop them in the teaching process at school. Local wisdom are parts of local culture which can be understood as a human effort by using their cognitions to act and behave as the response to something, object, or an event that occurs in a particular space. The method used in this study is a meta-analysis of empirical studies done by the researcher since 2005 in Bali. Eastern communities (Balinese - Indonesian in particular) have a worldview which is very different from that of the eastern communities (Euro-American) being the places where the culture of sciences was born. The students who live in the eastern cultural environment will find it difficult to learn science at the school since the indigenous culture does not receive enough attention and is different from what they learn in science.